Function of P2X4 Receptors Is Directly Modulated by a 1:1 Stoichiometric Interaction With 5-HT3A Receptors - Soto, Paola; Gaete, Pablo S.; Fuentes, Christian; Lozano, Benjamin; Naulin, Pamela A.; Figueroa, Xavier F.; Barrera, Nelson Patricio (Frontiers in Cellular Neuroscience, 2020)
Interacting receptors at the neuronal plasma membrane represent an additional regulatory mode for intracellular transduction pathways. P2X4 receptor triggers fast neurotransmission responses via a transient increase in intracellular Ca2+ levels. It has been proposed that P2X4 receptor interacts with 5-HT3A receptor in hippocampal neurons, but their binding stoichiometry and the role of P2X4 receptor activation by ATP on this crosstalking system remains unknown. Via pull-down assays, total internal reflection fluorescence microscopy measurements of the receptors colocalization and expression at the plasma membrane, and atomic force microscopy imaging, we have demonstrated that P2X4/5-HT3A receptor complexes can interact each other in a 1:1 stoichiometric manner that is preserved after ATP binding. In addition, macromolecular docking followed by 100 ns molecular dynamic simulations suggested that the interaction energy of P2X4 receptor with 5-HT3A receptor is similar at holo and apo state of P2X4 receptor, and the interacting 5-HT3A receptor decreased the ATP binding energy of P2X4 receptor. Finally, the P2X4 receptor-dependent Ca2+ mobilization is inhibited by the 5-HT3A interacting receptor. Altogether, these findings provide novel molecular insights into the allosteric regulation of P2X4/5-HT3A receptor complex in lipid bilayers of living cells via stoichiometric association, rather than accumulation or unspecific clustering of complexes.